Mental Health Status in Women Who Marry at an Early Age in Kampung Tubanan Baru, Block N Surabaya - Wahjuningtijas, Rindang (Side: Scientific Development Journal, 2024)
Marriage is actually a sacred and beautiful thing that can be a precious moment in a person's life, but in reality living a household ark is not easy, the occurrence of early marriage often before emotional maturity is fully reached will cause heavy emotional pressure and risk as well, therefore the research using this case study method wants to examine how the quality of marriage and mental health status Women who marry at an early age, in completing this study using qualitative research, case studies with in-depth interview methods and observations, factors that affect the quality of marriage in women who marry at an early age, the role of mental health in maintaining the harmony of marriage relationships and steps taken to improve the quality of marriage and mental health in women who marry at an early age.